Perovskite-based mixed protonic-electronic conducting membranes for hydrogen separation: Recent status and advances - Wang, H.; Wang, X.; Meng, B.; Tan, X.; Loh, K.; Sunarso, J.; Liu, Shaomin (Elsevier, 2017)
Hydrogen share in the energy market has increased significantly in line with greater demand for zero emission fuel and the development of novel production routes via renewable resources. The application of mixed protonic-electronic conducting (MPEC) ceramic membrane within the hydrogen production process is an innovative route that enables high purity hydrogen production with low cost. This review provides readers a brief summary of the research efforts on MPEC ceramic membrane for hydrogen separation as well as the membrane reactor for hydrogen production and dehydrogenation or hydrogenation reactions. Most of the existing MPEC ceramic membranes come from either a single-phase or a dual-phase membrane. We discuss the working principles, the performances, the advantages and disadvantages, and the main issues of all these membranes. Major emphasis of the review is to cover the literature published in the last ten years since the earlier progress has been well documented by the previously existing reviews. We also put forward recommendations for future research direction in this topic.